Health inequality and economic disparities by race, ethnicity, and gender - Nicolò Russo; Rory McGee; Mariacristina De Nardi; Margherita Borella; Ross Abram (The Institute for Fiscal Studies (IFS), 2024)
We measure health inequality during middle and old age by race, ethnicity, and gender and evaluate the extent to which it can explain inequalities in other key economic outcomes using the Health and Retirement Study data set. Our main measure of health is frailty, which is the fraction of one's possible health deficits and is related to biological age. We find staggering health inequality: At age 55, Black men and women have the frailty, or biological age, of White men and women 13 and 20 years older, respectively, while Hispanic men and women exhibit frailty akin to White men and women 5 and 6 years older. The health deficits composing frailty reveal that most health deficits are more likely for Black and Hispanic people than for White people, with the notable exception of those requiring a diagnosis. Imputing medical diagnoses to Black and Hispanic people uncovers even larger health gaps, especially for Black men. Health inequality also emerges as a powerful determinant of economic inequality. If Black individuals at age 55 had the health of their White peers, the life expectancy gap between these two groups would halve, and the gap in disability duration would decrease by 40-70%. Other outcomes are similarly affected by health at age 55, indicating that targeted health interventions for minority groups before middle age could substantially reduce economic disparities in the quantity and quality of life.
Keywords: 330; Health; Gender; Ethnic group; Black people; White people; Social inequality; Income distribution; United States; Gesundheit; Geschlecht; Ethnische Gruppe; Schwarze Menschen; Weiße; Soziale Ungleichheit; Einkommensverteilung; USA